2018
DOI: 10.5114/ada.2017.71358
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subcutaneous methotrexate on markers of metabolic syndrome in psoriatic patients – preliminary report

Abstract: IntroductionMethotrexate (MTX) has anti-proliferative and anti-inflammatory effects in psoriasis. Moreover, low doses can reduce the risk of developing cardiovascular diseases. It turns out that psoriasis and atherosclerosis have a similar pathogenetic mechanism: the same pro-inflammatory cytokines, Th1 and Th17, are involved in both diseases.AimTo evaluate the effects of metabolic markers, protective cytokines (interleukin 10 (IL-10), transforming growth factor β (TGF-β)) and a marker of endothelial damage (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
(51 reference statements)
1
17
0
3
Order By: Relevance
“…Maia et al, which observed metabolic syndrome in Brazilian ankylosing spondylitis patients and Papadakis et al, which observed metabolic syndrome in male Greek ankylosing spondylitis patients reported that the prevalence of metabolic syndrome was 27% and 34.9%, respectively [7,11]. The differences between this study and previous studies might be due to treatment differences because all of the patients in this study received csDMARDs which did not affect metabolic syndrome's parameters directly like anti-TNFα which was used in some of the previous studies [25].…”
Section: Discussionmentioning
confidence: 64%
“…Maia et al, which observed metabolic syndrome in Brazilian ankylosing spondylitis patients and Papadakis et al, which observed metabolic syndrome in male Greek ankylosing spondylitis patients reported that the prevalence of metabolic syndrome was 27% and 34.9%, respectively [7,11]. The differences between this study and previous studies might be due to treatment differences because all of the patients in this study received csDMARDs which did not affect metabolic syndrome's parameters directly like anti-TNFα which was used in some of the previous studies [25].…”
Section: Discussionmentioning
confidence: 64%
“…Early diagnosis and effective treatment protect patients from complications and severe consequences of the musculoskeletal system. In order to understand the exact etiopathogenesis of this disease, its early detection and effective treatment, various biomarkers specific to this disease are investigated [1,[4][5][6][7][8]. According to the National Institutes of Health Biomarkers Definitions Working Group, a biomarker is "a characteristic that is objectively measured and evaluated as an indicator of normal biological processes, pathogenic processes, or pharmacologic responses to therapeutic intervention" [9].…”
Section: Introductionmentioning
confidence: 99%
“…In 24 patients with plaque psoriasis, 12-week treatment with subcutaneous methotrexate caused a trend towards an increase in IL-10, but not TGF-β, concentrations. 60 In patients with chronic heart failure, 12-week treatment with methotrexate significantly increased the plasma concentrations of IL-10. 89 A significant increase in IL-10 concentrations after 4- or 12-week methotrexate treatment was reported in rabbit models of in-stent neo-atherosclerosis and cardiac allograft vasculopathy, and in post-myocarditis rats.…”
Section: Putative Mechanisms Mediating the Effects Of Methotrexate Agmentioning
confidence: 99%
“…Contrasting results have been reported on the capacity of methotrexate to influence the activity of the cholesterol efflux protein and the concentrations of total cholesterol and different lipoproteins. 49 60 More recently, a study in cholesterol-fed rabbits receiving combined treatment with lipid core nanoparticles containing paclitaxel and methotrexate showed a significant regression of aortic plaque and intima areas. This was associated with a reduction of macrophage presence in aortic lesions, matrix metalloproteinase 9, and TNF-α gene expression when compared to control animals.…”
Section: Methotrexate and Cardiovascular Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation